Bone mineral density is associated with Vitamin D related rs6013897 and estrogen receptor polymorphism rs4870044: The Tromsø study - Martinaityte, Ieva; Jorde, Rolf; Emaus, Nina; Eggen, Anne Elise; Joakimsen, Ragnar Martin; Kamycheva, Elena (PLOS ONE, 2017)
Source at http://doi.org/10.1371/journal.pone.0173045 Background: Bone mineral density (BMD) is determined by bone remodeling processes regulated by endocrine, autocrine and genetic mechanisms. Thus, some studies have reported that BMD is associated with single nucleotide polymorphisms (SNPs) associated with vitamin D receptor (VDR), serum 25(OH)D levels and estrogen receptor 1 (ESR1), but without consensus. Therefore, we aimed to map and compare the risk genotypes for forearm and total hip low BMD. Methods and findings: Data were derived from a population-based study in northern Norway; the Tromsø Study. Distal forearm BMD was measured with a single x-ray absorptiometric device, while total hip BMD was measured with a dual-energy x-ray absorptiometric device. There were 7,317 and 4,082 successful analyses of distal forearm and total hip BMD, respectively, and at least one SNP of interest. We evaluated plausible BMD modulating factors and associations of BMD and SNPs related to vitamin D metabolism (FokI, Cdx2, BsmI, rs2298850, rs10741657, rs3794060, rs6013897), ApaI-BsmI-TaqI haplotypes and ESR1 SNP rs4870044. Results: Age, BMI, physical activity and smoking were significantly associated with BMD. In a linear regression model with adjustment for age and gender and with the major homozygote as reference, rs6013897 had a standardized beta coefficient (β) of –0.031 (P = 0.024) for total hip BMD. β for ESR1 SNP rs4870044 was –0.016 (P = 0.036) for forearm BMD and –0.034 (P = 0.015) for total hip BMD. The other SNPs nor serum 25(OH)D were significantly associated with BMD. Conclusions: Both forearm and total hip BMD were associated with ESR1 SNP rs4870044. Of the vitamin D–related genes, only CYP24A1 gene rs6013897 was associated with total hip BMD, but the association was weak and needs confirmation in other studies. Serum 25(OH)D was not associated with BMD in our population, probably due to the generally sufficient vitamin D levels in the population.